Technological capacity-building and technology partnership : field findings country experiences and programmes - United Nations; United Nations Conference on Trade and Development (Geneva : United Nations Conference on Trade and Development, 1995)
The information material is a collection of papers prepared for the workshop on selected cooperation aspects for technological capacity-building in developing countries
opc 20/12/2016
Loans
Keywords: Diffusion of innovations -- Economic aspects; Technological innovations -- International cooperation -- Economic aspects; Technology -- Economic aspects; Technology transfer; Economic development; Developing countries